One-pot pyrolysis of metal-embedded biochar derived from invasive plant for efficient Cr(VI) removal. Issue 4 (August 2021) - Liang, Jinye; Chen, Yaozhong; Cai, Miao; Gan, Min; Zhu, Jianyu
Abstract: In this work, metal-embedded Eichhornia crassipes derived biochar (BC, Fe-BC, Al-BC, NH-BC) was synthesized through one-step pyrolysis to remove Cr(VI) from aqueous solution. The effects of initial pH, adsorption kinetics, adsorption isotherms and competitive experiments were measured. SEM, XRD, FTIR showed that metals successfully embedded BCs. Raman indicated metal-embedded BCs are characterized by a greater extent of the disorder in aromatic ring structure than original BCs. The Cr(VI) removal was dependent on pH. The maximum adsorption capacity of Fe-BC500 was 47.72 mg/g under pH value of 2.0. In additions, the adsorption of Cr(VI) followed the Pseudo First Order kinetics and the Langmuir model, demonstrating that the adsorption process was controlled by chemical and monolayer adsorption. The intraparticle diffusion models showed adsorption was affected by many factors. In the Cr(VI) competitive system, Cu(II) and citric acid are favorable for Cr(VI) removal, while phosphate anion retarded Cr(VI) removal. Electrochemical analysis revealed that Fe-BC500 exhibited the lowest electrical resistance and the fastest electron transfer rate. The Cr(VI) removal mechanism on metal-embedded BCs included electrostatic attraction, surface complexation and redox reaction. Therefore, metal-embedded invasive plant derived biochar are of great significance to remove Cr(VI) from aqueous solution. Graphical Abstract: ga1 Highlights: Metal-embedded invasive plant derived biochar through one-step pyrolysis. Fe-BC was the most effective in the removal of Cr(VI) among metal-embedded biochar. Highly pH-dependent was presented in Cr(VI) removal by all prepared biochar. Cr(VI) was removed via electrostatic attraction, complexation and redox reaction.